CULTURAL FEATURES OF VERBAL EXPRESSIONS IN ENGLISH AND UZBEK COMMUNICATION - Eshmirzayeva, Nozima; Mavjuda , Bolibekova Mardiyevna (Educational Research in Universal Sciences, 2023)
This article is devoted to the study of cultural features of English and Uzbek communication. As these two languages belong to totally different different language families, they both also differ in terms of culture. The aim of this research paper is to identify and analyze similar as well as distinguishing features of both English and Uzbek culture and the use of verbal expressions in both culture. The object of this article is verbal expressions, whilst the subject matter is cultural features of English and Uzbek verbal expressions in communication. The results of the analyses are illustrated with a number of examples in English and Uzbek.